STUDENTSâ RESPONSES TO THE USE OF DRAMA TECHNIQUE IN LEARNING LITERATURE - ., Utut Kurniati (Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
This research aimed to investigatethe studentsâ motivation in learning Literature using drama technique, to show what kinds of difficulties faced by the students and to show the way how they overcome the problems. The subjects of the research wereall the fifth semester students in the academic years of 2014/2015 of UNSWAGATI. There were 12 classes. Each consisted of 25 students. The researcher took K and L class as the sample of her study by using lottre. It mean there were 50 students as the sample. Revering to the reseach questions and the findings, the researcher found that students had high motivation in lerning, facing some difficulties in the learning process like limited vocabularies, cultural gap, the length of the story and feeling shy to act. Concerning the problems, the students had done many solutions. They enriched their action by using gesture, asking their friends, opening notes, reading the script and wacthing the original videos. There are some suggestions to enhance and find the best way in teaching literature. Practically, in order to gain the learning objective more optimal, lecturer are expected to be more creative in finding drama and enrich the class by taching them cultural differences. For further researcher, drama is also possible to developeother language skills other than speaking. Keywords: Studentsâ Responds, Drama, Litereature